Attitudes towards complementary alternative medicine among Malaysian adults - Malina Jasamai, Farida Islahudin, Nur Farhah Samsuddin (Journal of Applied Pharmaceutical Science, 2017)
Complementary and alternative medicine (CAM) has become more popular in recent years. Psychosocial factors such as attitude towards CAM has been suggested as a predictor of CAM use in certain populations. This study investigated the association between attitude and CAM use among the local population. The questionnaire-based survey was performed prospectively among adults aged ≥18 years, with informed consent. Results demonstrated that a high number of respondents admitted to CAM use (n=297/417, 71.2%) compared with those that did not use CAM (n=117/417, 28.1%). The use of herbal products was the most popular CAM (n=227, 54.44%). The main reason for CAM use was recommendation from friends and family (n-217, 52%). The main reason for not using CAM was due to satisfaction with conventional medicines (n=106, 25.4%). Attitude scores demonstrated that respondents felt positive towards the need for pharmacists to equip themselves with sufficient CAM knowledge (3.04±0.032, maximum; 4). There was a positive correlation between the number of CAM used and total attitude score (ρ=0.102, p=0.036). In conclusion, personal attitude influenced their likelihood of using CAM among the local population. The need for appropriate advice on CAM use is reflected in the need for pharmacists’ community support.
Keywords: Complementary alternative medicine (CAM), attitude, herbal products, conventional medicines.